Kepuasan kerja memediasi pengaruh gaya kepemimpinan, budaya organisasi, dan motivasi terhadap kinerja karyawan Bank BTN kantor cabang Jakarta Kuningan - Sugiono, Edi; Nurwulandari, Andini; Dining, Yuniarta (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this study is to analyze and prove the influence of leadership style, organizational culture, motivation, job satisfaction on employee performance, and the influence of leadership style, organizational culture, motivation on job satisfaction, as well as the indirect influence of leadership style, organizational culture, and motivation on Employee performance is mediated by job satisfaction. In this study, it was proven that leadership style, organizational culture, motivation, job satisfaction had a positive and significant effect on employee performance, while leadership style, organizational culture, and motivation had a positive and significant effect on job satisfaction. For leadership style, organizational culture, and motivation indirectly also have a positive and significant effect on employee performance mediated by job satisfaction. Job satisfaction has the highest influence mediating motivation on employee performance, which means that if job satisfaction is increased, motivation will increase and have an impact on increasing employee performance.